Pelaksanaan Perjanjian Kredit dengan Jaminan Sertifikat Deposito Pada PT. Bank BRI Cabang Mataram - I Putu Bayu Aditya Nendra; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Jurnal Analogi Hukum, 2020)
Abstract—The deposit certificate according to bank Indonesia is proof of the debt issued by the bank for the amount of money entrusted to him for a certain period of time. Certificates of deposit issued can be purchased at per-sale at any time and can be played for a bank loan as well as PT. BRI Bank pays the mortgage by holding the original certificate of deposit guaranteed until the credit facility is paid off. The formulation of the problem in this study is as follows: how is the implementation of the credit agreement with collateral for deposit certificates at PT. BRI Bank Mataram Branch Office and how the legal consequences and method of settlement if the term deposit certificate has been completed, while the credit agreement is still running. In this study empirical legal research was used. The results of the discussion in this study are as follows: Implementation of credit agreements with collateral for deposit certificates at PT. BRI BANK Mataram Branch Office is carried out with several stages of the process that must be done to become a debtor at PT. BRI BANK, namely applying for credit, and signing credit. In implementing credit agreements with collateral/ collateral for deposit certificates at PT. BRI BANK prospective borrowers must have deposits in their own name, not on behalf of other people. The way to settle a deposit certificate with a shorter period of time compared to a credit agreement is where the bank will change the form of a certificate of deposit into an ARO (Auth Roll Over) certificate so that when the deposit certificate is due, the time period will automatically adjust to the credit period and the reimbursement are with the knowledge of the customer, if the debtor wants to apply for a loan with a guarantee of a certificate of deposit.